2020
DOI: 10.1136/ijgc-2020-001271
|View full text |Cite
|
Sign up to set email alerts
|

The upper limit of optimal tumor size in patients with FIGO 2018 stage IB2 cervical cancer undergoing radical hysterectomy

Abstract: ObjectivePatients who undergo radical hysterectomy may require postoperative adjuvant radiotherapy, and all efforts should be made to reduce dual therapy in such patients. The aim of this study was to determine the optimal upper limit of tumor size in patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB2 cervical cancer who undergo radical hysterectomy.MethodsWe retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This may be due to decreased parametrial involvement, as tumors < 2 cm had much lower parametrial involvement in a study of 461 stage IB patients 14 and have also shown a lower risk of being pathologically upstaged after surgical resection. 15 A study with stage IB1 patients showed that tumors larger than 2.7 cm were associated with increased risk factors like LVI or deep stromal invasion, 16 suggesting that increasing tumor size corresponds with and correlates with other poor histologic indices. In our cohort, earlier substages like stage IB1 receive primary surgical treatment at a higher proportion (65.9%) compared to stage IB2 or stage IB3 (33.3% and 8.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to decreased parametrial involvement, as tumors < 2 cm had much lower parametrial involvement in a study of 461 stage IB patients 14 and have also shown a lower risk of being pathologically upstaged after surgical resection. 15 A study with stage IB1 patients showed that tumors larger than 2.7 cm were associated with increased risk factors like LVI or deep stromal invasion, 16 suggesting that increasing tumor size corresponds with and correlates with other poor histologic indices. In our cohort, earlier substages like stage IB1 receive primary surgical treatment at a higher proportion (65.9%) compared to stage IB2 or stage IB3 (33.3% and 8.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%